The risk‐outcome‐experience triad: Mortality risk and the hospital consumer assessment of healthcare providers and systems survey. Issue 9 (2nd June 2016) - Cowen, Mark E.; Czerwinski, Jennifer; Kabara, Jared; Blumenthal, David U.; Kheder, Susan; Simmons, Stefanie
Abstract : BACKGROUND: Studies have shown an association between the Hospital Consumer Assessment of Healthcare Providers and Systems Survey (HCAHPS) scores and clinical quality. The mortality risk on admission predicts adverse events. It is not known if this risk also portends a suboptimal patient experience. OBJECTIVE: To determine if the admission mortality risk identifies an experience of care risk. DESIGN: A retrospectively assembled cohort in which individual HCAHPS survey responses were linked to the admission risk of dying. SETTING: Five community hospitals of various sizes in Michigan. PATIENTS: There were 17, 509 HCAHPS medical and surgical respondents; 2513 (14.4%) were at high risk of dying. MEASUREMENTS: Odds ratio (OR) (high‐risk patients to low‐risk patients) for providing a top box score for HCAHPS dimensions, controlling for hospital and the standard HCAHPS patient mix adjustment factors. RESULTS: High‐risk respondents were less likely to provide the most favorable response (unadjusted) for all HCAHPS domains, although the difference was not significant ( P = 0.09) for discharge information. Multivariable analyses indicated that high‐risk patients were less likely to report a top box experience for doctor communication (OR: 0.85; 95% confidence interval [CI]: 0.77‐0.94) and responsiveness of hospital staff (OR: 0.77; 95% CI: 0.69‐0.85), but were more likely to have received adequate discharge information (OR: 1.30, 95% CI: 1.14‐1.48). CONCLUSIONS: Patients at high risk of dying who completed surveys were less likely to report favorable physician communication and staff responsiveness. Further understanding of these relationships may help design a care model to improve both outcomes and experience. Journal of Hospital Medicine 2016;11:628–635. © 2016 Society of Hospital Medicine